INCOME SMOOTHING IN SHARIA ACCOUNTING: STUDY OF LITERATURE - Siregar, Tapi Rumondang (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Income smoothing is a process that manipulates the timing of earnings or earnings reports so that reported earnings look stable and good. Income smoothing usually occurs because the profit generated is not according to the company's expectations. Managers doing income smoothing basically want to get various economic and psychological benefits. The purpose of this study is to describe the literature on income smoothing in Islamic accounting for a period of five years, 2017-2022. The research method used in this study is qualitative research with content analysis of papers from the Google Scholar database. Researchers found 154 papers, after going through a selection process, the author finally reviewed 25 articles that were considered the most relevant. Researchers found four themes related to income smoothing in Islamic accounting, namely the influence factor of companies doing income smoothing, income smoothing behavior in Islamic banks, comparison of income smoothing behavior of Islamic banks with conventional banks and income smoothing in a Sharia perspective.